Prophylactic phage administration provides a time window for delayed treatment of vancomycin-resistant Enterococcus faecalis in a murine bacteremia model - Wang, Wei-Xiao; Yu, Jiao-Yang; Chen, Xiu-Zhen; Fu, Shi-Yong; Li, Hui; Yi, Peng-Cheng; Ren, Yun-Yao; Gu, Shuang-Lin; Gao, Jing-Han; Fan, Jing; Sun, Yan-Mei; Feng, Jie; et al. (Frontiers in Microbiology, 2025)
IntroductionVancomycin-resistant Enterococcus faecalis (VRE) poses a significant challenge in clinical settings due to its resistance to multiple antibiotics. Phage therapy offers a promising alternative to address this resistance crisis. However, critical gaps remain regarding optimal dosing, therapeutic design, and treatment timing for phage therapy targeting VRE-induced bacteremia.MethodsThe biological and genomic characteristics of a novel lytic phage specific to VRE were investigated. Its in vitro bactericidal and antibiofilm activities were evaluated, along with its synergy with antimicrobial agents. In vitro safety and protective efficacy were assessed using a mouse bacteremia model. The impact of phage therapy on gut microbiota was examined through 16S rDNA gene sequencing.ResultsWe isolated and characterized a novel lytic phage, vB_EfaS-1017, specific to vancomycin-resistant E. faecalis. This phage features a circular, double-stranded DNA genome (40,766 bp), sharing 91.19% identity and 79% coverage with Enterococcus phage vB_EfaS_SRH2. vB_EfaS-1017 exhibited robust bactericidal and antibiofilm activity in vitro and demonstrated synergy with levofloxacin. Safety assessments confirmed its non-toxicity to mammalian cells and lack of hemolytic activity. In a mouse bacteremia model, phage treatment alone rescued 60% of infected mice, while combining phage with levofloxacin increased survival to 80%. Prophylactic administration of phage 24 hours prior to infection failed to prevent mortality. However, a combination of prophylactic phage administration and delayed treatment rescued 60% of mice, compared to 100% mortality in the delayed treatment alone group. Additionally, phage therapy helped maintain or restore gut microbiota balance.DiscussionThese findings underscore the potential of phage-antibiotic combinations as a superior therapeutic strategy against VRE infections. The observed synergy between phages and antibiotics highlights a promising approach to overcoming bacterial resistance and improving clinical outcomes. Furthermore, prophylactic phage administration may provide a critical time window for effective delayed treatment. Further preclinical research is essential to refine phage therapy protocols for clinical application.